2022
DOI: 10.1021/acsanm.1c03555
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic Imidazolate Framework Nanoencapsulation of CpG for Stabilization and Enhancement of Immunoadjuvancy

Abstract: Metal–organic frameworks (MOFs) have been used to improve vaccine formulations by stabilizing proteins and protecting them against thermal degradation. This has led to increased immunogenicity of these proteinaceous therapeutics. In this work, we show that MOFs can also be used to protect the single-stranded DNA oligomer CpG to increase its immunoadjuvancy. By encapsulation of the phosphodiester CpG in the zinc-based MOF, zeolitic imidazolate framework-8, the DNA oligomer is protected from nuclease degradation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
(101 reference statements)
0
21
0
Order By: Relevance
“…[5][6][7][8][9] Since the rst report on the construction of MOF-based vaccine synthesized by biomimetic mineralized growth of ZIF-8 onto the surface of ovalbumin (OVA) and attaching the cytosine-phosphate-guanine oligodeoxynucleotides (CpG ODNs) in/on ZIF-8, the exploration of ZIF-8 in the delivery of vaccine antigens has been attracting more attention. [10][11][12][13][14][15] Research efforts have demonstrated that in addition to the typical advantages of ZIF-8 in drug delivery, the MOF-based vaccine platform also exhibited adjuvant effects by stabilizing antigens, 11 promoting antigen presentation, 10 codelivering other adjuvants 14,16 and inducing multiple immune responses. 15 Encouraged by the successes in the synthesis and delivery of OVA@ZIF-8 vaccine, researchers started trying to synthesize viral vaccines by encapsulating various types of viral antigens, including virus-like particles, live viruses, and viral vectors into ZIF-8.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Since the rst report on the construction of MOF-based vaccine synthesized by biomimetic mineralized growth of ZIF-8 onto the surface of ovalbumin (OVA) and attaching the cytosine-phosphate-guanine oligodeoxynucleotides (CpG ODNs) in/on ZIF-8, the exploration of ZIF-8 in the delivery of vaccine antigens has been attracting more attention. [10][11][12][13][14][15] Research efforts have demonstrated that in addition to the typical advantages of ZIF-8 in drug delivery, the MOF-based vaccine platform also exhibited adjuvant effects by stabilizing antigens, 11 promoting antigen presentation, 10 codelivering other adjuvants 14,16 and inducing multiple immune responses. 15 Encouraged by the successes in the synthesis and delivery of OVA@ZIF-8 vaccine, researchers started trying to synthesize viral vaccines by encapsulating various types of viral antigens, including virus-like particles, live viruses, and viral vectors into ZIF-8.…”
Section: Introductionmentioning
confidence: 99%
“…27 Frasconi et al synthesized an enzyme− nanozyme hydrogel composite with cascade catalysis properties for the analysis of glucose in human serum samples, 28 while Gassensmith and coauthors prepared functional zeoliticimidazolate-framework-based carriers for encapsulation of the single-stranded DNA oligomer CpG to increase its immunoadjuvancy. 29 Yang and co-workers found enhanced luminescence and self-driven gelation from a pyrene-modified pillar [5]arene nanostructure for potential imaging applications. 30 Bulut and Yilmaz reported quercetagetin-integrated silver nanoparticles for morin oxidation, affording dosedependent cytotoxicity to selected cell lines.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Pérez-García et al developed nanofiber-containing supramolecular hydrogels to increase the bioavailability of curcuminoids for the treatment of inflammatory skin diseases . Frasconi et al synthesized an enzyme–nanozyme hydrogel composite with cascade catalysis properties for the analysis of glucose in human serum samples, while Gassensmith and coauthors prepared functional zeolitic-imidazolate-framework-based carriers for encapsulation of the single-stranded DNA oligomer CpG to increase its immunoadjuvancy . Yang and co-workers found enhanced luminescence and self-driven gelation from a pyrene-modified pillar[5]­arene nanostructure for potential imaging applications .…”
Section: Nanosystems For Healthcarementioning
confidence: 99%
“…[11, 12] ZIFs are unique as polymeric materials due to their kinetic lability; phosphate and carbonate salts, or albumin-rich environments readily pull the zinc from the framework causing it to dissolve completely, returning the original antigen to its pristine state. [13, 14] ZIF’s versatility in capturing, preserving, and releasing antigens is exceptional and has been used to encapsulate whole viruses,[15, 16] bacteria,[17] proteins,[18, 19] DNA,[20, 21] RNA,[22] yeast,[23] liposomes,[24, 25] enzymes,[26, 27] glycans,[28] and carbohydrates. [29] We have recently shown that ZIF-encapsulated formulations exhibit a depot effect, which significantly enhances the efficacy of vaccine models.…”
Section: Introductionmentioning
confidence: 99%